DAMPAK PERUBAHAN SOSIAL BUDAYA TERHADAP PENDIDIKAN - Anisa Trirezeki; Fitrina Fitrina; Ubabudin Ubabudin (CV. ADIBA AISHA AMIRA, 2025)
Sociocultural change is a complex phenomenon that has a significant impact on various aspects of human life, including the education system. This research aims to describe the impact of socio-cultural changes on education and identify the implications that arise in the context of modern education. This study uses a qualitative approach by analyzing relevant literature and empirical data to understand how changes in cultural values, norms, and social structures influence educational practices. Sociocultural changes have a complex and multi-dimensional impact on education. Changes in cultural values can influence educational goals and curricula, while changes in social norms can influence the dynamics of teacher- student relationships and between students in the classroom. Additionally, changing social structures can create new challenges in achieving inclusivity and equality in education. The implications of these changes require adaptation of education systems to ensure that education remains relevant, inclusive, and empowers future generations.